Dimensi kebahagiaan golongan dewasa Melayu / Khairudin Che Tak - Khairudin , Che Tak (2017)
This study aims to identify the dimension of happiness in Malay adults. There are two main issues of this study. First, is the exploration of the dimensions of happiness, and second, evaluation of the scale of Malay happiness, which is adapted from an existing scale. To tackle these two issues, three specific studies were conducted. The studies were exploration of happiness dimensions, reinforcement of the dimension of happiness and the psychometric scale of happiness in Malay adults. The studies involved 45, 30 and 1283 respondents in the first, second and third study, respectively. Qualitative methods which were focus group interview and semi structured interview were used in the first and second study, respectively. A quantitative method (survey) was used in the third study to test the Malay Happiness Scale. Results of NVivo analysis indicated that the happiness of the Malay consisted of 12 dimensions, which were, family relations, good relationships with others, life achievement, religion, being positive, harmonious environments, acceptance (redha), autonomy, knowledge, leisure activities, health, and standard of living. As predicted, all dimensions were found to be related to Malay traditional values and the principles of Islam. The results also showed that the family relations were the main contributor to the happiness of the Malays, either qualitatively or quantitatively. In terms of psychometric, it was found that the instrument that was designed to measure the Malay happiness was unidimensional, has high internal consistency of reliability (α=0.95) and good validity (convergent validity; overall life satisfaction (r=0.72), Personal Well-Being Index (r=0.84) and Satisfaction with Life Scale (r=0.64); divergent/discriminant validity; Rosenberg Self-Esteem Scale (r=0.32)). Overall, this study has shown that the dimensions of the Malay happiness are still closely related to the collectivistic values. There were also other culturally-related dimensions of happiness such as acceptance (redha), gratitude and budi. These dimensions of happiness illustrate the distinctiveness of the Malay customs, traditional values and Islamic teachings, which have been passed down from generation to generation. In terms of measurement, it was found that the Malay Happiness Scale has high applicability onto other studies as it has high reliability and validity.